Investigating Minimum Acceptable Diet and Infant and Child Feeding Index as indicators of stunting in children aged 6-23 months - Suryadi Limardi; Dini Mutia Hasanah; Ni Made Dwiyathi Utami; I Gusti Lanang Sidiartha (Paediatrica Indonesiana, 2020)
Background The complementary feeding period of 6-24 months of age is one of the most crucial moments in child growth, in which most of the decline in length-for-age Z-score (LAZ) occurs. The Minimum Acceptable Diet (MAD) and Infant and Child Feeding Index (ICFI) are indicators to assess complementary feeding practices in the children with potential for stunting. Objective To assess and compare the usefulness of MAD and ICFI scores as indicators of inadequate feeding practice on stunting in children aged 6-23 months. Methods This case-control study was conducted in South and West Wewewa subdisctricts of Southwest Sumba, East Nusa Tenggara, Indonesia, from February to August 2019. Participants were children aged 6-23 months who had received complementary feeding for a minimum duration of one month. Children with LAZ <-2 were allocated into the case group (stunted) and those with LAZ>-2 into the control group. Both MAD and ICFI scores were assessed in both groups. ICFI was categorized as low, average, and high. The association between complementary feeding practice which depicted by the MAD and ICFI scores and stunting was measured using logistic regression. Results Of 322 participants, 161 children were allocated into each group. Multivariate analysis revealed that those in low and average ICFI tertile had higher odds of stunting [(OR 2.85; 95%CI 1.35 to 6.00; P<0.01) and (OR 1.95; 95%CI 1.09 to 3.46; P<0.05), respectively]. No association was found between MAD and stunting. Conclusion Inadequate complementary feeding practice is found to increase the risk of stunting among children aged 6-23 months. Compared to MAD, ICFI is a better indicator in demonstrating an association between complementary feeding practice and stunting.